GOVERNANCE DEVELOPMENT OF PUJON KIDUL'S VILLAGE TOURISM - Natcha Longkul; Wanwisa - Wongpon; Wepawee Burana; Dara Fitria Melani Putri; Alliya Safitri; Ach. Apriyanto Romadhon (Jurnal Partisipatoris, 2020)
This research is a qualitative research study. This research aims to 1) study important factors in the development of the tourist village of Pujon Kidul 2) study sought to answer how Pujon Kidul drives the development of a tourism village. Data were collected using in- depth interviews. Discussions from key informants such as a head of Pujon Kidul village, and non-participatory interviews. The study results show that the governance of the development of the Pujon Kidul tourism village has 4 important factors for development: 1) Human Capital most people in the village receive the training of working skills resulting from the cooperation of nearby villages to have skills in the problems encountered are that the people in the village have an education at the elementary level. Therefore is an obstacle to development 2) Local Participation is led by the head of the village that is the main determinant and determination the people in the village cooperate and follow the leader. 3) Financial Management the development budget of the village is mainly from the capitalization of the people in the village, beginning with the head of the village. 4) Managerial Skill the head of the village has used strategic management by able to manage village development including the development of the agricultural and resources of the village to increase value. Governance of the development of Pujon Kidul tourism village the most encouraging factors are local participation and managerial skills both factors are ready for development. People in the village are active and involved in development. Including the ability of the leader to create a point of sale for the community, planning, decisions, and add value to community resources as for the other two factors is still a management difficulty in human capital, people still lack access to basic education which is an important foundation local governments should emphasize and attend of this and financial management factors lack government support which is considered as the main factor in the development.